2020
DOI: 10.3748/wjg.v26.i37.5534
|View full text |Cite
|
Sign up to set email alerts
|

Review of inflammatory bowel disease and COVID-19

Abstract: The first cases of a novel corona virus infection were reported in Wuhan China in December of 2019, followed by the declaration of an international pandemic by the World Health Organization in March 2020. Early reports of the virus, now known as severe acute respiratory syndrome coronavirus 2, and its clinical disease coronavirus disease 2019 (COVID-19), has shown higher rates of morbidity and mortality in the elderly and those with pre-existing medical conditions. Of particular concern is the safety of those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…In IBD patients, older age in combination with comorbidities, are found to be a risk factor for severe COVID-19. A possibly higher risk for patients with UC compared to CD is also found [3,5]. Interestingly, our findings revealed that IBD patients <50 years had more concerns about medical treatment and COVID À 19 compared to those !50 years.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In IBD patients, older age in combination with comorbidities, are found to be a risk factor for severe COVID-19. A possibly higher risk for patients with UC compared to CD is also found [3,5]. Interestingly, our findings revealed that IBD patients <50 years had more concerns about medical treatment and COVID À 19 compared to those !50 years.…”
Section: Discussionmentioning
confidence: 55%
“…These patients have regular and frequent visits, thus the restrictions due to the pandemic may have the greatest personal impact and are most intrusive. It is likely that IBD patients in general and those on immunosuppressive therapy in particular would be concerned about their own health and the risk of being infected by SARS-CoV-2 and develop COVID-19 [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the prevalence of IBD among COVID-19 patients was found to be 1.2%, and an age greater than 66-years-old was a strong independent predictor[ 48 ]. Similarly, low rates have also been reported in pediatric IBD patients in Europe, China, Canada, Israel, and South Korea[ 42 ].…”
Section: Resultsmentioning
confidence: 95%
“…During the pandemic, particular concern has been raised in populations with the highest risk, such as the elderly and patients with preexisting medical conditions, with a specific focus on inflammatory bowel disease (IBD)[ 42 ], a gastroenterological disease caused by immune dysregulation. Upregulated expression of ACE-2 in the inflamed mucosa as well as a soluble form of ACE-2 circulating in the blood of IBD patients has been found[ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite our important findings, several limitations must be considered [ 6 ]. First, some studies also included highly suspicious cases in their COVID-19 cohort.…”
Section: Discussionmentioning
confidence: 99%